CONTROL OF VIBRATION PARAMETERS ON THE TANK WALL OF OIL POWER TRANSFORMERS IN OPERATION - Maxmudov, Bekzod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Summary The experimental results of determining the oil viscosity by controlling the vibration parameters in the operational state of the oil power transformer were presented. According to the vibration parameters, the indicators of reduction of the dynamic viscosity from the nominal value are determined. During the current technical inspection of transformers, it was possible to determine the condition parameters in a short period of time and at low costs.